2015
DOI: 10.1186/s12876-015-0323-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical course and outcome of acute pancreatitis according to the two main etiologies: alcohol and gallstone

Abstract: BackgroundStudies concerning clinical course and outcome of acute pancreatitis (AP) according to etiologies were rare, especially after year 2000. This study was designed to investigate the difference between the clinical course of alcoholic and biliary AP.MethodsOf the 153 patients diagnosed as AP with a first attack between January 2011 and January 2013, extensive clinical data of 50 patients with AP caused by alcohol and 76 patients with AP caused by gallstone were analyzed retrospectively. We compared the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
57
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 27 publications
3
57
1
1
Order By: Relevance
“…Similar results were observed in the current study, where 97.3% of males had alcohol‐induced AP, while 93.7% females had GS‐related AP. Alcohol‐induced AP was found in a relatively younger population compared to the GS‐related AP in this study (37.08 ± 9.9 vs 43.29 ± 14.8; P < 0.001), as also demonstrated in various other studies . Recurrent attacks of pancreatitis were evidently found in a higher percentage of patients with alcohol‐related, than GS‐related, AP (11.4 vs 5.2%, P = 0.011), as had been established in previous studies .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Similar results were observed in the current study, where 97.3% of males had alcohol‐induced AP, while 93.7% females had GS‐related AP. Alcohol‐induced AP was found in a relatively younger population compared to the GS‐related AP in this study (37.08 ± 9.9 vs 43.29 ± 14.8; P < 0.001), as also demonstrated in various other studies . Recurrent attacks of pancreatitis were evidently found in a higher percentage of patients with alcohol‐related, than GS‐related, AP (11.4 vs 5.2%, P = 0.011), as had been established in previous studies .…”
Section: Discussionsupporting
confidence: 90%
“…Recent studies also demonstrate varying data. Cho et al , in an analysis of 126 patients, found a significantly higher percentage of persistent OF in the alcohol group compared to the biliary group. Zhu et al reported differences between the two groups with regard to the young and middle‐aged patients but not in the elderly.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…[8][9][10] Severity scoring systems for acute pancreatitis assign the same parameters, but there is evidence that etiology or patient phenotype may also affect disease outcome. [12][13][14] In contrast, the effect of ABP on hospital outcomes in patients with cirrhosis is unknown. [12][13][14] In contrast, the effect of ABP on hospital outcomes in patients with cirrhosis is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…They are more commonly seen in patients with alcohol-associated pancreatitis (20%) than with gallstone pancreatitis (6.6%)[3]. Although most commonly immediately peripancreatic or intrapancreatic, they can occur in truly extrapancreatic locations throughout the peritoneal cavity as well as the mediastinum[4,5].…”
Section: Introductionmentioning
confidence: 99%